Meningkatkan Kerja Sama Siswa Melalui Model Pembelajaran Kooperatif Two Stay Two Stray Pada Mata Pelajaran Fikih - Abdur Rohman; Badi'ul Marom; Hamdan Adib (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2026)
Teamwork is a central competency in 21st-century learning and constitutes one of the primary objectives of Physics education, integrating aspects of cognitive, social, and moral development. This study aimed to examine the effectiveness of the cooperative learning model Two Stay Two Stray (TSTS) in enhancing students’ teamwork skills in Physics learning. The study employed a quantitative approach with a quasi-experimental design using a non-equivalent control group design involving two Grade XI classes, namely the experimental group (XI A) and the control group (XI B). Students’ teamwork skills were measured using a validated instrument. Data were analyzed using an independent sample t-test and normalized gain (N-Gain). The findings revealed a statistically significant difference in posttest scores between the two groups (t = 15.26; p < 0.001). Furthermore, the experimental group demonstrated a moderate improvement category (N-Gain = 0.584), whereas the control group showed only a low level of improvement (N-Gain = 0.063).